Metachromatic Leukodystrophy: Diffusion MR Imaging Findings - Sener, R. Nuri (AJNR Am J Neuroradiol, 2002)
Summary: Herein the case of a 10-month-old boy with metachromatic leukodystrophy is reported. Diffusion MR imaging performed with an echo-planar trace sequence revealed a cytotoxic edema-like pattern (high signal intensity on b = 1000 s/mm(2) images and low apparent diffusion coefficient values) in the affected white matter in the absence of an ischemic condition. This finding was unchanged at a 6-month follow-up, as revealed by diffusion MR imaging. A gradient-echo diffusion sequence, reverse fast imaging in steady-state precession, revealed hyperintense changes at the corresponding regions. It is likely that the cytotoxic edematous pattern (restricted diffusion pattern) reflected restriction of mobility of the water molecules within abnormal portions of the myelin sheath, because impaired myelin breakdown and reutilization are known features of metachromatic leukodystrophy.